2005
DOI: 10.1111/j.1527-3466.2005.tb00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Colesevelam: Potential Uses for the Newest Bile Resin

Abstract: Colesevelam is the newest bile resin with a unique chemical structure. It binds to bile acids with higher affinity than traditional bile acid sequestrants and has fewer gastrointestinal side effects and drug interactions. Colesevelam is safe and efficacious alone or in combination with HMG-CoA reductase inhibitors (statins) in reducing low-density lipoprotein cholesterol (LDL-C) levels. Despite this, the role of colesevelam in the treatment of hyperlipidemia remains limited, particularly in the face of new lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…However, gastrointestinal side effects such as constipation, indigestion, dyspepsia, and flatulence are very common and together with the high doses required (15–30 g/day) adversely affect patient compliance and the efficacy of these agents. The recent development of a higher affinity bile acid binder Colesevelam decreased the required dose (Steinmetz and Schonder 2005), but the efficacy, patience compliance, and side effect profile still favors the use of statins as a first-line therapy. Based on its remarkable substrate specificity and expression on the intestinal brush border membrane, blocking the ASBT using high affinity, nonabsorbable inhibitors represented an attractive strategy and alternative to the sequestrants for treatment of hypercholesterolemia (Kramer and Glombik 2006).…”
Section: Development Of Asbt Inhibitorsmentioning
confidence: 99%
“…However, gastrointestinal side effects such as constipation, indigestion, dyspepsia, and flatulence are very common and together with the high doses required (15–30 g/day) adversely affect patient compliance and the efficacy of these agents. The recent development of a higher affinity bile acid binder Colesevelam decreased the required dose (Steinmetz and Schonder 2005), but the efficacy, patience compliance, and side effect profile still favors the use of statins as a first-line therapy. Based on its remarkable substrate specificity and expression on the intestinal brush border membrane, blocking the ASBT using high affinity, nonabsorbable inhibitors represented an attractive strategy and alternative to the sequestrants for treatment of hypercholesterolemia (Kramer and Glombik 2006).…”
Section: Development Of Asbt Inhibitorsmentioning
confidence: 99%
“…The peak effects of colesevelam HCL on lipid parameters occur in the first 2 weeks of administration based on early reductions in LDL-C noted in clinical trials [46,47] . Davidson et al [48] demonstrated an LDL-C lowering effect of 19.1% after 6 weeks of administration with colesevelam HCL 3.75 g daily.…”
Section: Pharmacodynamicsmentioning
confidence: 98%
“…The maximum of [ 14 C] colesevelam HCL in whole blood was estimated to be 0.04% (0.17 ± 0.10 (µg Eq)/ml) at 72 h post dose. Colesevelam HCL has little to no volume of distribution, plasma protein binding, metabolism and renal clearance [27,46,47] .…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%
“…BASA promote apo-A1 synthesis by an unknown mechanism and tend to raise HDL levels. [44] Three BASA are currently available [ Table 3]. Their use has been hindered by inconvenient dosing and by unpleasant side effects (e.g., constipation).…”
Section: Management Managementmentioning
confidence: 99%